2011
DOI: 10.3892/or.2011.1526
|View full text |Cite
|
Sign up to set email alerts
|

Chondroitin sulphate enhances the antitumor activity of gemcitabine and mitomycin-C in bladder cancer cells with different mechanisms

Abstract: Abstract. Non-muscle invasive bladder cancer is the most common type of bladder cancer in Western countries. The glycosaminoglycan (GAG) layer at the bladder surface non-specifically blocks the adherence of bacteria, ions and molecules to the bladder epithelium and bladder cancer cells express CD44 that binds GAG. Currently, there are few options other than cystectomy for the management of non-muscle invasive bladder cancer with intravesical chemotherapy using several drugs such as gemcitabine (GEM) and mitomy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 20 publications
(19 reference statements)
0
8
0
Order By: Relevance
“…Thus, although chondroitin sulfate has been used for decades as a dietary supplement and a symptomatic slow acting drug, only recently it has been demonstrated that it is readily degraded and fermented in vitro by human gut microbes, suggesting that it may act as a prebiotic (Shang et al, 2016). In addition, it is well acknowledged that chondroitin sulfate negatively regulates cancer cell signaling (Willis and Klüppel, 2014) and enhances the activity of conventional chemotherapeutics (Ferro et al, 2012), a finding that is consistent with the observation that sulfated motifs of chondroitin sulfate inhibit triple negative breast cancer (Poh et al, 2015). In a peculiar synergism with Kluyveromyces marxianus, chondroitin sulfate inhibits inflammation (Vallières and du Souich, 2010) and is endowed with immune-stimulating properties consisting in the activation of macrophages without inducing the production of pro-inflammatory cytokines (Wrenshall et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, although chondroitin sulfate has been used for decades as a dietary supplement and a symptomatic slow acting drug, only recently it has been demonstrated that it is readily degraded and fermented in vitro by human gut microbes, suggesting that it may act as a prebiotic (Shang et al, 2016). In addition, it is well acknowledged that chondroitin sulfate negatively regulates cancer cell signaling (Willis and Klüppel, 2014) and enhances the activity of conventional chemotherapeutics (Ferro et al, 2012), a finding that is consistent with the observation that sulfated motifs of chondroitin sulfate inhibit triple negative breast cancer (Poh et al, 2015). In a peculiar synergism with Kluyveromyces marxianus, chondroitin sulfate inhibits inflammation (Vallières and du Souich, 2010) and is endowed with immune-stimulating properties consisting in the activation of macrophages without inducing the production of pro-inflammatory cytokines (Wrenshall et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Members of the CHST family also mediate inflammation, immunity, angiogenesis, and extracellular matrix reorganization 63,64. So far there is one study 65 that reports the involvement of chondroitin sulfates in enhancing antitumor activity of gemcitabine in human bladder cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…CS is a ligand for CD44 [ 43 ] and it protects chronic lymphocytic leukemia (CLL) cells from apoptosis [ 45 ]. Combination of CS with gemcitabine strongly inhibited human bladder cancer cells growth [ 46 ]. CS-g-poly copolymers can be self-assembled into micelles in water and then used to encapsulate camptothecin.…”
Section: Structure and Function Of Cd44mentioning
confidence: 99%